Altered Interoceptive Processing in Generalized Anxiety Disorder—A Heartbeat-Evoked Potential Research - Pang, Jiaoyan; Tang, Xiaochen; Li, Hui; Hu, Qiang; Cui, Huiru; Zhang, Lanlan; Li, Wei; Zhu, Zhuoying; Wang, Jijun; Li, Chunbo (Frontiers in Psychiatry, 2019)
Generalized anxiety disorder (GAD) is one of the most common anxiety disorders. Interoception, particularly heartbeat perception, plays an important role in the pathophysiology of anxiety disorders. However, the neural mechanisms underlying abnormal heartbeat perception in GAD remain insufficiently understood. In the present study, patients with GAD and healthy control subjects underwent an eye-close (EC) resting state (interoceptive) and eye-open (EO) resting state (exteroceptive) without paying conscious attention to heartbeat. Electrocardiography (ECG) and electroencephalography (EEG) signals were recorded at the same time. Our results show that interoceptive and exteroceptive state changes fail to modulate the amplitude of heartbeat-evoked brain potentials (HEPs) in patients with GAD. Further analysis revealed a marginally larger HEP in the EO states than in the EC states only in patients with GAD. Finally, the right prefrontal HEP amplitude was significantly correlated with anxiety levels of the patients only in the interoceptive state. Our results suggest that deficient adaptation to interoceptive signals and altered interoception inference play important roles in the manifestation of anxiety.